A intencionalidade linguística e os aspectos de oralidade nas campanhas publicitárias de instituições de ensino em outdoors nas cidades de Recife e Olinda - Mafra, Heloisa Pedrosa de Araújo (2012)
This work shows the entries of the oral language perceived in advertising campaigns of educational institutions, on billboards, advertising its courses, with the purpose of interacting with their consumer audience. As linguistic contribution, the work is based on the teachings of Marcuschi, in Textual Linguistics, and in Koch theoretical proposals, aiming at the investigation of Intertextuality in building expressive outdoor, on texts produced by different schools. It also sought to examine how these messages are elaborated to the dissemination of services offered in different billboards, identifying the characteristics of the genre as well as the importance of understanding and acceptance by the target audience. The work has as goal the provision of data for the study on the preparation of billboards. So, it was observed details of expressions, in addition to the lexical choices carried out to draw the attention of the reading public, the offers in different courses. In addition, it was observed how messages are targeted to a specific audience, making use of a proper language, aiming to the enthusiasm and satisfaction of the target audience, in location, time and purpose in disclosure.